2011
DOI: 10.1111/j.1530-9290.2011.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Waste Costing as a Catalyst in Pollution Prevention Investment Decisions

Abstract: This article presents a case study in a Nigerian firm of how waste costing can be applied to pollution prevention (P2) investment decisions. This case is informed by the priority accorded to P2 as a preferred alternative to end-of-pipe pollution control. It demonstrates that even in the absence of effective regulations in a developing country, cost accounting can spur P2 decisions by management through the system of waste cost allocation. The case used standard cost data from the Wonder Beauty Care Company and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
3
0
1
Order By: Relevance
“…Ngwakwe (2011) discovered a relationship between pollution prevention investment and waste costing in Nigerian firms. Similarly, Agustia et al (2019) found a link between the prevention strategy on firm value with EMA as an intervening variable in Indonesian manufacturing firms.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Ngwakwe (2011) discovered a relationship between pollution prevention investment and waste costing in Nigerian firms. Similarly, Agustia et al (2019) found a link between the prevention strategy on firm value with EMA as an intervening variable in Indonesian manufacturing firms.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…In response to growing public attitude towards environmental issues, the organisations are working alongside environmental experts to find solution for pollution abatement and achieve success (Clarke and Fuller 2010). Adoption of green practices restores natural balance, protects health of workers and consumers, enhances operational efficiencies, improves financial performance of firms and helps in gaining competitive strength (Ngwakwe 2011). As a strategic business issue, corporate greening operations are based on 3R principles-reduce, recycle and reutilisation to gain competitive strength in manufacturing (Hoque and Clarke 2013;Jabbour et al 2012;Kopnina 2017).…”
Section: Corporate Greening Practicesmentioning
confidence: 99%
“…Pollution denotes evidence of inefficient use of resources enhancing waste and resource depletion. Pollution prevention is one of the foremost challenges to manufacturing organisations to reduce or eliminate the waste at the source (Freeman et al 1992;Ngwakwe 2011;Pollution Prevention report 1992). Pollution prevention eliminates waste at the source by bringing some alterations in the existing process, encouraging usage of non-hazardous materials.…”
Section: Pollution Prevention Practices In Industriesmentioning
confidence: 99%
“…Η ρύπανση και η υποβάθμιση του φυσικού περιβάλλοντος υποδηλώνουν αναποτελεσματική χρήση πόρων. Η πρόληψη της ρύπανσης είναι επομένως μία από τις πρωταρχικές προκλήσεις για τις επιχειρήσεις προκειμένου να αντιμετωπιστεί εν τη γενέσει της η επιβάρυνση του περιβάλλοντος από τις δραστηριότητές τους (Ngwakwe, 2011). Η πρόληψη της ρύπανσης καταπολεμά την επιβάρυνση του περιβάλλοντος επιφέροντας αλλαγές στις υφιστάμενες διαδικασίες και ενθαρρύνοντας τη χρήση μη επιβλαβών για το περιβάλλον υλικών (Rehman & Shrivastava, 2013).…”
Section: έννοια και είδη της περιβαλλοντικής στρατηγικήςunclassified